Pengaruh Kemampuan Mengelola Emosi terhadap Konsentrasi Belajar Siswa di SMA Negeri 3 Kota Jambi - Qodriyah Qodriyah; Akmal Sutja; Hera Wahyuni (Departement of Mathematics Education, 2023)
This study aims to reveal how big the percentage of the ability to manage emotions and concentration in learning, as well as the influence of the ability to manage emotions on the concentration of students in SMA Negeri 3 Jambi City. Concentration of learning, namely the ability of students to focus on thoughts and actions during the learning process by setting aside unrelated things. The ability to manage emotions is the ability of individuals to handle their emotions so that they can be expressed appropriately and do not interfere with their activities. This type of research is quantitative with the ex post facto method of data collection techniques, namely using a questionnaire with validity and reliability tests to determine the determination of the instrument. The data analysis technique used Formula C, normality test, linearity test, simple regression analysis with the help of SPSS 25. The sampling technique used stratified random sampling with a total sample of 266 students of class X and XI. The findings of this study can be concluded that in general the ability to manage students' emotions includes recognizing emotions, knowing the causes of emotions, being able to find alternative ways of dealing with emotions, being able to determine how to deal with emotions, emotions expressed appropriately are at a moderate percentage (59%), student learning concentration which includes concentrating, paying attention and carrying out learning according to the objectives is at a moderate percentage (57%). The influence between the two variables is classified as quite strong (23.2%). Guidance and counseling teachers should be able to assist students in maintaining and improving their ability to manage their emotions so that student learning concentration can also be even better.